MODAL INTELEKTUAL, KEPEMILIKAN INSTITUSIONAL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - Nurramayuningsih Nurramayuningsih; Mujibah A. Sufyani (JRAK, 2020)
Knowledge and intangible assets become the important source of competitive advatage for company (knowledgw-based economy). The study aims was to investigate the effect of intellectual capital, institutional ownership to profitability and firm value. Sample used were 6 manufacturing companies of sub sectors consumer goods industry listed on the Indonesia Stock Exchange from 2012 to 2017, with purposive sampling, secondary data, and panel data regression analysis. The results indicated that simultaneous intellectual capital and institutional ownership affected financial performance. Partially intellectual capital had a positive and significant effect on financial performance, but institutional ownership did not have significant effect. Financial performance has a positive and significant effect on firm value. Intelectual capital had an important roles to increase performance and value of the firm.